The Dialectic of the Clavichord: Review essay - Palsmar, Henrik (Danish Yearbook of Musicology, 2019)
Review of: Andrew Talle: Beyond Bach. Music and Everyday Life in the Eighteenth Century. Urbana: University of Illinois Press, 2017.